2017
DOI: 10.1176/appi.ajp.2017.16091072
|View full text |Cite
|
Sign up to set email alerts
|

PTSD Psychotherapy Outcome Predicted by Brain Activation During Emotional Reactivity and Regulation

Abstract: Objective Exposure therapy is an effective treatment for posttraumatic stress disorder (PTSD), but many patients will not respond. Brain functions governing treatment outcome are not well characterized. Here, we examined brain systems relevant to emotional reactivity and regulation, constructs thought to be central to PTSD and exposure therapy effects, to identify the functional traits of individuals most likely to benefit from treatment. Methods Individuals with PTSD underwent functional magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 46 publications
7
103
1
Order By: Relevance
“…Although the invasiveness of DBS is likely to mean that such treatments would be reserved for only the most intractable of cases, the use of TMS has been steadily increasing as a therapeutic tool in psychiatry. The mechanisms by which TMS might exert its effects to mediate symptom improvement in PTSD remain unclear; however, the concurrent combination of TMS with electroencephalography (EEG) or fMRI is becoming a powerful technology for identifying pathological changes in brain functional network connectivity and predicting the efficacy of the treatment 161,162 . The hope of using more targeted methodologies to modulate circuits remains.…”
Section: Unifying Themes and Future Directionsmentioning
confidence: 99%
“…Although the invasiveness of DBS is likely to mean that such treatments would be reserved for only the most intractable of cases, the use of TMS has been steadily increasing as a therapeutic tool in psychiatry. The mechanisms by which TMS might exert its effects to mediate symptom improvement in PTSD remain unclear; however, the concurrent combination of TMS with electroencephalography (EEG) or fMRI is becoming a powerful technology for identifying pathological changes in brain functional network connectivity and predicting the efficacy of the treatment 161,162 . The hope of using more targeted methodologies to modulate circuits remains.…”
Section: Unifying Themes and Future Directionsmentioning
confidence: 99%
“…While considered an essential step in understanding the neural substrates of PE, the use of a waiting list as a control group can only provide a partial answer to the effects of PE on rsFC. As suggested by the Fonzo et al (2017), it remains unclear whether the observed post-treatment functional changes reflected a normalization of neural abnormalities or compensatory neural adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…Psychotherapy research in posttraumatic stress disorder (PTSD) has recently begun using neuroimaging methods to assess structural (Helpman, Papini, et al, 2016) and functional (Fonzo, Goodkind, Oathes, Zaiko, Harvey, Peng, Weiss, Thompson, Zack, Lindley, et al, 2017; Helpman, Marin, et al, 2016) neural alterations of evidence-based treatments. Prolonged Exposure (PE) therapy is a relatively brief, highly structured, exposure-based treatment, considered to be effective in treating PTSD (Bradley, Greene, Russ, Dutra, & Westen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, another recent study did not find evidence of EN and DMN coactivation and inhibition of SN emotional reactivity; instead, the authors reported increased anterior prefrontal cortex activation only in a cognitive reappraisal task, not in emotional reactivity or conflict tasks, and only following prolonged exposure TMP, not for waitlist controls. This was associated with a reduction in hyperarousal symptoms but not reexperiencing or avoidance symptoms, as well as improved psychological well‐being (Fonzo et al., ). Moreover, TMP was associated with increased connectivity by the EN with the SN, leading to a reduction in the intensity of arousal and emotional reactivity (Fonzo et al., ).…”
Section: Ptsd Neuroimaging Research Of Relevance For Tmpmentioning
confidence: 99%
“…This was associated with a reduction in hyperarousal symptoms but not reexperiencing or avoidance symptoms, as well as improved psychological well‐being (Fonzo et al., ). Moreover, TMP was associated with increased connectivity by the EN with the SN, leading to a reduction in the intensity of arousal and emotional reactivity (Fonzo et al., ). The anterior prefrontal cortex is involved simultaneously in attention to the external environment and internal processing and potentially serves a coordinating function for cognitive reappraisal and emotion regulation activities undertaken by the EN and DMN.…”
Section: Ptsd Neuroimaging Research Of Relevance For Tmpmentioning
confidence: 99%